Influence of Hydrostatic Pressure on the Formation of Voids in Gelled Crude Oil - Chala, Girma T.; Sulaiman, Shaharin A.; Japper-Jaafar, Azuraien; Kamil Wan Abdullah, Wan Ahmad (Applied Science and Engineering Progress, 2022)
Production of waxy crude oil from offshore fields has increased in the last decade. However, the operation is being challenged with the high wax content of crude oil that tends to precipitate at a lower temperature. This paper presents the effects of hydrostatic pressure on the voids formed in waxy crude oil gel. A flow loop rig that simulates offshore waxy crude oil transportation was used to produce the gel. A Magnetic Resonance Imaging of the 3-Tesla system was used to scan the gelled samples in horizontal and vertical pipes. The hydrostatic pressure effect was found to be the most significant near the pipe wall because a change in percent voids volume of 0.53% was observed in that region. In particular, the voids volume reduction was more pronounced in the lower half side of the pipe. The total volume of voids in the vertical pipe was lower than that in the horizontal pipe, and this suggests that the gel in the vertical pipe became denser due to the effects of the hydrostatic pressure. Conversely, the voids volume around the pipe core in the vertical pipe was higher when compared to that in the horizontal pipe. The change in voids volume near the pipe core and wall shrunk to a minimum and converged to 0.18% voids volume at a larger duration of the hydrostatic effect. Further, hydrostatic pressure was observed to have significant influences for the higher duration, making the void size distributed across and along the pipeline. However, it was found to have insignificant effects on voids size distribution for smaller duration. The findings of this study can help for a better understanding of voids formation in vertical pipelines that would further assist in developing a model predicting restart pressure accurately.